2008
DOI: 10.3928/01484834-20080401-06
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Nurse Education Level and Patient Safety: An Integrative Review

Abstract: The relationship between patient safety and nurse education level has implications for current and prospective nurses, hospital administrators, policy makers, and nurse educators. This integrative literature review assesses the current state of science on the topic during a 20-year period, using the Agency for Healthcare Research & Quality's Patient Safety Indicators to measure outcomes. Twenty-four studies of variable quality were included. Although studies suggest that increasing RN dose (i.e., number of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…Factors include increased patient acuity (Aydin et al, 2015;Blegen & Vaughn, 1998), high nurse/patient ratio and workload (Aiken, Clarke, Sloane, Sochalski, & Silber, 2002;Aydin et al, 2015;Blegen, Goode, & Reed, 1998;Blegen & Vaughn, 1998;Cho et al, 2003;Cox, et al, 2015;Everhart, et al, 2014;Needleman, Buerhaus, Mattke, Stewart, & Zelevinsky, 2000;Tzeng & Yin, 2008;Whitman et al, 2002) and insufficient number of assistive personnel (Aydin et al, 2015;Bae, et al, 2014;Blegen & Vaughn, 1998;Cox, et al, 2015;Spetz et al, 2007;Tzeng & Yin, 2008). Several studies have suggested that increasing the number of nursing staff can result in decreased falls, yet few studies specifically included level of nurse experience (Aiken, Clarke, Cheung, Sloane, & Silber, 2003;Aydin et al, 2015;Halm, et al, 2005;McGillis-Hall, Doran, & Pink, 2004;Ridley, 2008).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Factors include increased patient acuity (Aydin et al, 2015;Blegen & Vaughn, 1998), high nurse/patient ratio and workload (Aiken, Clarke, Sloane, Sochalski, & Silber, 2002;Aydin et al, 2015;Blegen, Goode, & Reed, 1998;Blegen & Vaughn, 1998;Cho et al, 2003;Cox, et al, 2015;Everhart, et al, 2014;Needleman, Buerhaus, Mattke, Stewart, & Zelevinsky, 2000;Tzeng & Yin, 2008;Whitman et al, 2002) and insufficient number of assistive personnel (Aydin et al, 2015;Bae, et al, 2014;Blegen & Vaughn, 1998;Cox, et al, 2015;Spetz et al, 2007;Tzeng & Yin, 2008). Several studies have suggested that increasing the number of nursing staff can result in decreased falls, yet few studies specifically included level of nurse experience (Aiken, Clarke, Cheung, Sloane, & Silber, 2003;Aydin et al, 2015;Halm, et al, 2005;McGillis-Hall, Doran, & Pink, 2004;Ridley, 2008).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The data from 10 renal units in Scotland [15] showed that the nurse-to-patient ratio ranged from 1:7.1 to 1:29.8 and was not associated with peritonitis rates. Although these results suggest that the individual clinical workloads of nursing staff who provide training, retraining and general support to PD patients is not a dominant factor in determining peritonitis rates, other important considerations in relation to nurse trainers may include clinical experience [29], educational levels [30] and the proportion of specialist nurses within a PD unit [31].…”
Section: Who Should Provide Pd Training?mentioning
confidence: 99%
“…The relationship between a degree and improved methods of critical thinking, a larger knowledge base, and competence should be evaluated with regard to the level of influence of nursing experience 17 . In 2004 the majority of the nursing population (42.2%) had an associate degree as an initial preparation degree compared to 30.5% for baccalaureate preparation and 0.5% for master's and higher degrees 6 .…”
Section: Perceived Barriersmentioning
confidence: 99%